The electrochemical cleavage of the nitrobenzoyl group from butyl nitrobenzoates in N,N-dimethylformamide - Jorge, SMA; Stradiotto, N. R. (Elsevier B.V., 1996)
The applicability of the nitrobenzoyl group [NO2C6H4CO-] to protecting the functional hydroxyl group was investigated through study of the electrochemical behaviour of the butyl 4-, 3- and 2-nitrobenzoate compounds. These isomers are reduced in two cathodic steps. The first, at potentials of ca. -0.9 V vs. SCE, is attributed to the formation of rather stable anion radicals, involving one-electron transfer. The second, at potentials of ca. -1.7 V vs. SCE, occurs with a two-electron transfer in an ECE process, in which the dianion produced undergoes scission of the C-O bond giving n-butanoate ions with high yields (similar to 80%)
Keywords: electrochemical cleavage; nitrobenzoyl; butyl nitrobenzoates